2019
DOI: 10.3390/ijms20174186
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination by Single-Particle Cryo-Electron Microscopy: Only the Sky (and Intrinsic Disorder) is the Limit

Abstract: Traditionally, X-ray crystallography and NMR spectroscopy represent major workhorses of structural biologists, with the lion share of protein structures reported in protein data bank (PDB) being generated by these powerful techniques. Despite their wide utilization in protein structure determination, these two techniques have logical limitations, with X-ray crystallography being unsuitable for the analysis of highly dynamic structures and with NMR spectroscopy being restricted to the analysis of relatively sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 143 publications
(226 reference statements)
0
31
1
Order By: Relevance
“…The electron image can be recorded, with minimal electron dose on the specimen, using a highly efficient electron detector [95]. The thousands of images of the same molecule or molecular assembly at different orientations around the viewing direction can then be recombined by the relatively new technique of single particle analysis [96] to yield the structure of the specimen with resolutions around 1 to 3 Å [89,94,95,96,97]. It is noteworthy that the 2017 Nobel Prize for Chemistry was awarded to Drs.…”
Section: Methods Of Studying the Crossbridge Cyclementioning
confidence: 99%
“…The electron image can be recorded, with minimal electron dose on the specimen, using a highly efficient electron detector [95]. The thousands of images of the same molecule or molecular assembly at different orientations around the viewing direction can then be recombined by the relatively new technique of single particle analysis [96] to yield the structure of the specimen with resolutions around 1 to 3 Å [89,94,95,96,97]. It is noteworthy that the 2017 Nobel Prize for Chemistry was awarded to Drs.…”
Section: Methods Of Studying the Crossbridge Cyclementioning
confidence: 99%
“…Thus, steric zippers with a short inter-sheet distance exist, but resolution of their structure has started to become possible only in the last few years due to methodological advances (cryo-EM). 38…”
Section: Validationmentioning
confidence: 99%
“…These values are normally less than 10% and are expected to remarkably increase in frequency in the presence of a detectable effect the ∆G D -D upon mutation. Ever since the discovery of IDPs, it has been observed that these proteins in isolation may retain a considerable amount of embryonic structure [50][51][52][53], which may considerably vary from case to case and can be experimentally addressed with different experimental techniques such as NMR or SAXS [54][55][56]. Therefore, since mutagenesis may potentially perturb these structures, when evaluating IDPs as candidates for the Φ values analysis, it is important to take into account these possible effects.…”
Section: The Residual Structure Of Idpsmentioning
confidence: 99%